PREVALENCE OF HEREDITARY SPASTIC PARAPLEGIA IN ADULTS - Muhammad Hanan Zafar 1 , Aamir Gul Memon2 , Muhammad Umer Atif3 , Sidra Zafar4 Aqsa Naveed5 , Muhammad Sanaullah6, Mehran Akram7, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2022)
ABSTRACT INTRODUCTION: The hereditary spastic paraplegia (HSP) is a condition which includes different neurological diseases showing a genetically and heterogeneous clinically. HSP is a condition with different types, influence the lower extremity with advancement of disease shows spasticity or weakness, and some other symptoms of bowel and bladder dysfunctions involvement. HSP is hereditarily heterogeneous, and in excess of 20 hereditary types have been recognized. OBJECTIVE: The purpose of this study was to find the prevalence of hereditary spastic paraplegia in adults and association of other symptoms of disease like bowel and bladder dysfunctions, distal muscle atrophy, dystonia etc. METHODS: A cross-sectional observational study was conducted on 80 subjects presenting with different neurological diseases which fall in the criteria of hereditary spastic paraplegia. Data was collected from different hospital settings in Lahore through non-probability convenient sampling technique. Clinical questionnaire for hereditary spastic paraplegia was used for data collection. RESULTS: There were 43 (53.8%) male and 37 (46.3%) female patients. Total prevalence of hereditary spastic paraplegia in adults were 3.75%. The prevalence of adult males with hereditary spastic paraplegia were 2.50% and 1.25% in adult females. The most commonly reported symptoms in HSP patients were distal muscle atrophy of lower limb (28.75%) and dystonia (12.5%) according to the study. CONCLUSION: This study concluded that the total prevalence of hereditary spastic paraplegia was very low in adults and mostly male are affected according to this study